Effective potential for non-coupled stochastic partial differential equations - Franceschini, Pedro; González, Luís; Muñoz íngel; Sierra Porta, David; Soldovieri, Terenzio (Ciencia)
We provide an Effective Potential Formulation for non-coupled (i.e. independent) Stochastic Partial Differential Equations with additive noise using the Hojman et al. method for writing the associated Lagrangean function. We show that this Potential is able to reproduce all the dynamics of the system, once a special differential operator has been applied. This procedure can be used to study the equilibria cases, the complete time evolution and spatial inhomogeneities of the system under consideration